Pengelolaan Limbah Tailing PT. Freeport Indonesia: Dampak Lingkungan Dan Tinjauan Hukum - Danny P. Hutagalung; Dalen Darbec Anew; David Harlingan (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The issue of mining waste from PT Freeport Indonesia has become a complex and controversial environmental problem, particularly regarding the disposal of tailings through the Aghawagon and Ajkwa Rivers and their placement in the Modified Ajkwa Deposition Area (ModADA), covering 230 km² in Papua. This study aims to analyze the environmental impacts, relevant regulations, and the implementation of waste management by PT Freeport Indonesia. The research employs a normative juridical analysis with an environmental regulation approach, as well as an empirical review of the social and ecological impacts of tailings disposal. The findings indicate that although PT Freeport operates under a Contract of Work and holds waste management permits, its tailings disposal practices have resulted in ecosystem changes in the rivers, sedimentation, and disruptions to indigenous communities in affected areas. Existing regulations, such as Law No. 32 of 2009 on Environmental Protection and Management and Government Regulation No. 101 of 2014 on Hazardous and Toxic Waste Management, have not been fully adhered to in tailings management implementation. This study recommends strengthening government oversight, increasing corporate responsibility in environmental restoration, and adopting a more sustainable approach to tailings management. Additionally, an evaluation of the Contract of Work and stricter environmental regulations should be enforced to ensure that mining industry practices are not only economically beneficial but also environmentally sustainable and socially responsible.